1995
DOI: 10.1126/science.270.5237.802
|View full text |Cite|
|
Sign up to set email alerts
|

Superior Parietal Cortex Activation During Spatial Attention Shifts and Visual Feature Conjunction

Abstract: Positron emission tomography was used to measure changes in the regional cerebral blood flow of normal people while they searched visual displays for targets defined by color, by motion, or by a conjunction of color and motion. A region in the superior parietal cortex was activated only during the conjunction task, at a location that had previously been shown to be engaged by successive shifts of spatial attention. Correspondingly, the time needed to detect a conjunction target increased with the number of ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
389
2
6

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 672 publications
(460 citation statements)
references
References 21 publications
53
389
2
6
Order By: Relevance
“…However, this effect was more pronounced when the left visual hemi®eld was attended. Such a hemispheric asymmetry has been frequently reported in spatial visual attention tasks using VEPs (Palmer and Tzeng, 1990;Posner and Petersen, 1990;Posner and Dehaene, 1994;Heilman, 1995) and PET (Corbetta et al, 1993(Corbetta et al, , 1995. In their study, Corbetta et al (1993) reported an asymmetrical activation of the parietal cortex when attending the left or right visual ®eld.…”
Section: Discussionsupporting
confidence: 55%
“…However, this effect was more pronounced when the left visual hemi®eld was attended. Such a hemispheric asymmetry has been frequently reported in spatial visual attention tasks using VEPs (Palmer and Tzeng, 1990;Posner and Petersen, 1990;Posner and Dehaene, 1994;Heilman, 1995) and PET (Corbetta et al, 1993(Corbetta et al, , 1995. In their study, Corbetta et al (1993) reported an asymmetrical activation of the parietal cortex when attending the left or right visual ®eld.…”
Section: Discussionsupporting
confidence: 55%
“…However, recently, Luo, Greenwood, and Parasuraman (2001) found that shifts in the spatial scale of attention, as elicited by variations in cue size in a search task, modulated early-latency ERP components (P1 and N1) recorded from scalp regions overlying posterior cortical areas. These results indicate that the spatial scale of attention also acts as a sensory gain control mechanism, as does attention shifting.Using PET in an uncued search task, Corbetta et al (1995) found that in comparison to feature search, conjunction search was associated with activation of the parietal lobe in a region closely overlapping the same region they had previously shown to be involved in covert shifts of attention. Furthermore, brain-damaged individuals with deficits in covert orienting are slower to search for targets defined by a conjunction of color and orientation, but are unimpaired for detection of either feature in isolation (Arguin, Joanette, & Cavanagh, 1993).…”
mentioning
confidence: 84%
“…However, most natural visual scenes are not as impoverished as this task. The visual search task provides a better analog to such everyday visual tasks.Behavioral (Treisman, 1996) and neuroimaging studies (Corbetta, Shulman, Miezin, & Petersen, 1995) suggest that the covert attention mechanism also operates in visual search tasks. However, the area containing a target in a search array may be large or small and attention may need to be distributed broadly or narrowly.…”
mentioning
confidence: 99%
“…Previous fMRI studies on dimension changes found significant activation of multiple posterior brain areas (e.g., Pollmann et al, 2000: fusiform gyrus, lateral occipital gyrus, superior/middle temporal gyrus, SPL and precuneus; Pollmann et al, 2006: IPS, fusiform gyrus, striate/peristriate cortex and posterior putamen/claustrum) that have been implicated in early attentional processes (Corbetta et al, 1993(Corbetta et al, , 1995(Corbetta et al, , 2000Corbetta & Shulman, 1999;Kelley et al, 2008;Macaluso et al, 2000;Nobre et al, 1997, Vandenberghe et al, 2000Yantis et al, 2002). Hence, it was concluded that dimension changes interfere with attention shifts to the target.…”
Section: Theoretical Implicationsmentioning
confidence: 99%